The Audience Motivation of Movie-Induced Tourism: an Indonesia Case Study - Parahiyanti, Cesya Rizkika; Purwanto, BM (JDM (Jurnal Dinamika Manajemen), 2021)
This research aims at identifying movie-induced tourism in terms of business related to audience personal motivation using a study on movie Ada Apa Dengan Cinta (AADC) 2. It uses qualitative research with a descriptive approach. The in-depth interviews from 17 informants are analyzed using conventional content analysis that would later raise the emergent themes to support the identification of movie-induced tourism in the study of AADC 2. The results of this study indicate that AADC 2 has a function to influence audiences traveling decisions on the featured locations after watching the movie, even though the film itself is not intended to promote a particular destination. This study’s audience’s personal motivations are grouped into two, namely general personal motivation and specific personal motivation. The audiences also revealed some additional considerations, such as accessibility and cost, in visiting the locations that influence their travel decision. It would be beneficial for a destination to incorporate filming into destination marketing plans by seeing a good case practice from AADC 2 movie with these results.